Least Cost Computer-aided Design of Steel Girders - Anderson, Katherine E.; Chong, Ken P. (Engineering Journal, 1986)
Hybrid steel beams, used for over a quarter of a century, have evolved through many theories of design criteria. In this paper, emphasis is placed on stiffened hybrid girders, although unstiffened and homogeneous girders are also included as special cases. AISC has developed specifications to which a steel member must perform. The formulas in the specifications, however, do not define explicitly the best girder to do a particular structural task. Instead, a "region" is defined which contains a large number of acceptable girders from which the designer must choose. Even when a computer is used for the design, unless special programming is implemented, the output is an acceptable non-optimized region from which the final choice is made. By equipping the design procedure with the ability to rank the acceptable choices by cost or weight, an optimized girder can be located within the region. This ranking process should include the cost and availability factors for several steel grades so that a hybrid girder, having the lowest cost, can be found. Likewise, by including labor costs for manufacturing steel girders, the feasibility of using web stiffeners can also be determined. The innovative design method which follows incorporates the AISC Specifications5 and extends the techniques developed by Ken P. Chong for unstiffened built-up steel sections. The goal of the design process is to define the geometry of the girder by optimizing a particular function, which, in this case, is the depth of the girder.